Antigua and the Antiguans: a full account of the colony and its inhabitants from the time of the Caribs to the present day, interspersed with anecdotes and legends : also, an impartial view of slavery and the free labour systems, the statistics of the island, and biographical notices of the principal families, Volume 1TT - (Saunders and Otley, 1844)
Culture et mode de vie des Antiguais aux 18e et 19e siècles.